PEMANFAATAN TEPUNG BIT (Beta vulgaris) DALAM PEMBUATAN BAKPAO ISI BULGOGI SEBAGAI MAKANAN SELINGAN SUMBER ZAT BESI DAN TINGGI SERAT PANGAN - Gita Ayu Nurwada Chalifaturrachim; Mira Sofyaningsih (ARGIPA (Arsip Gizi dan Pangan), 2022)
Beets are an abundant food ingredient in Indonesia, containing iron and dietary fiber which can prevent anemia and heart disease, reduce obesity, and reduce the risk of diabetes mellitus. The abundant use of wheat flour necessitates the import of wheat-based flour which does not grow in Indonesia, so beets which are processed into flour can reduce dependence on wheat flour while providing natural coloring. Bakpao is one of the snacks that are easy to consume and are liked by all ages. This research includes the manufacture of beetroot flour and the formulation of bakpao filled with bulgogi with the addition of beetroot flour F0 (0%), F1 (25%), F2 (30%), F3 (35%), and F4 (40%) with a completely randomized design (RAL) one treatment. The analysis carried out in this study included organoleptic analysis using a hedonic test involving 50 consumer panelists and chemical analysis (moisture content, ash content, carbohydrates, protein, fat, iron, and fiber) of selected bulgogi filled buns. Data analysis used the Kruskall Wallis test, if the p-value < 0.05 then continued with the Man Whitney test. The selected bulgogi stuffed bun was formulation 1 with a value of 18.916. The nutritional content of the selected formulation (F1) per 100 g has a water content of 42.33 g, ash content 1.90 g, protein 12.02 g, fat 7.89 g, carbohydrates 35.86 g, total energy 262.53 kcal, energy from fat 71.01 kcal, iron 4.49 mg, and dietary fiber 7.61 g. The bakpao filled with bulgogi produced can be claimed as a source of iron and high in dietary fiber.